Financial statement analysis - Foster, George (Englewood Cliffs, N.J. : Prentice-Hall, 1978)
This book provides an intensive study of financial statement analysis. This area has undergone marked change as researchers have utilized developments in accounting and the related disciplines of economics, finance, and statistics.
Includes bibliographical references and indexes.
hza 03/09/2018
Loans
Keywords: Financial statements